The Agile Consultant Guiding Clients to Enterprise Agility - Freedman, Rick (Apress : Imprint: Apress, 2016)
Learn the agile philosophy of lean processes, incremental delivery, deep client participation, decentralized authority, and just-in-time planning to bring speed, creativity, empowerment and increased productivity to product development. This book is your guide to becoming the go-to advisor for the enterprise agile transition. Many organizations have brought in agile coaches and achieved great progress in software development productivity, only to find teams slipping back into old methods as they encounter enterprise resistance and dysfunction. The consultative skills required to engage at the enterprise level differ greatly from those needed to coach teams in agile practices. Agile coaches and consultants need to up their game to successfully partner with executives, managers, and PMOs to evolve from traditional methods to a lean, agile mindset. The Agile Consultant, by former Intel Worldwide Project Management Director and agile expert Rick Freedman, author of Amazon best-seller The IT Consultant, shows how to overcome transition challenges and move beyond team-level practice coaching to guide the entire organization to enterprise agility. The Agile Consultant explains not only the basics of agile thinking, but also how to: Instill effective agile practices across the enterprise Coach teams, managers, and executives in learning, adopting, and practicing lean and agile strategies Diagnose the roadblocks and obstacles most organizations encounter during the transition to agile Use recognized change-management techniques to guide the enterprise to agility while minimizing disruption and resistance Navigate the many challenges that can derail the transition to agility Demonstrate the critical mix of facilitation, interpersonal, and relationship skills to help organizations succeed with agile Guide the corporate culture toward agility from the top down and the bottom up Evolve from old school project management thinking to a lean, agile mindset Agile methods are displacing traditional, process-heavy project management techniques, and are poised to migrate from software development to the rest of IT, and to the entire enterprise. Agile's rapid adoption proves a simple truth: agility works! Agile methods are here to stay, and will continue to expand within the organization. Enterprises are rapidly moving beyond agile development to agile IT, agile marketing, and agile strategic planning. Enterprises need agile coaches and consultants to guide them towards achieving the benefits of agility.